Clinical utility of leflunomide for BK polyomavirus associated nephropathy in kidney transplant recipients: A multicenter retrospective study. Issue 2 (1st March 2019) - Keller, Nicolas; Duquennoy, Simon; Conrad, Anne; Fafi‐Kremer, Samira; Morelon, Emmanuel; Bouvier, Nicolas; Moulin, Bruno; Hurault De Ligny, Bruno; Caillard, Sophie
Abstract: Background: BK polyomavirus associated nephropathy (BKPyVAN) is a significant clinical issue in kidney transplant (KT) recipients. No specific therapy is currently available, although treatment with leflunomide may be part of the therapeutic strategy. Here, we sought to examine the impact of leflunomide on the evolution of BKPyVAN. Methods: This was an observational retrospective study conducted in 3 French transplant centers. KT recipients who developed BKPyVAN and received leflunomide after failure of other treatment approaches were deemed eligible. Graft function, viral clearance, patient survival, rejection rates, treatment tolerability, and immunosuppression levels served as the main outcome measures. Results: A total of 55 patients were included. Treatment with leflunomide was started after a mean of 1.4 ± 4.1months  after BKPyVAN diagnosis. Between the introduction of leflunomide and the end of follow‐up, creatinine levels increased by 31 ± 118% ( P  = 0.04), whereas viremia decreased by 79 ± 37% ( P  < 0.001). Blood viral clearance was observed in 76% of the study patients. Rejection episodes occurred in 33% of the participants. Eleven patients lost their graft (9 of which because of BKPyVAN). Ten patients developed adverse effects and 3 discontinued leflunomide. Conclusion: We cannot conclude about the exact place of leflunomide in the therapeutic strategy of BKPyVAN. It may be a part of the therapy to promote BK polyomavirus clearance in cases of BKPyVAN who fail to improve after immunosuppression lowering alone. Unfortunately, a significant decline in renal function and high rejection rates remain major clinical challenges.